Transformation of Sucrose to Starch and Protein in Rice Leaves and Grains under Two Establishment Methods - Manisha Kumari; Bavita Asthir (Rice Science, 2016)
Six rice varieties, PR120, PR116, FengAiZan, PR115, PAU201 and Punjab Mehak 1 were raised under aerobic and transplanting conditions to assess the effects of planting conditions on sucrose metabolising enzymes in relation to the transformation of free sugars to starch and protein in flag leaves and grains. Activities of sucrose synthase, sucrose phosphate synthase and acid invertase increased till flowering stage in leaves and mid-milky stage (14 d after flowering) in grains and thereafter declined in concomitant with the contents of reducing sugar. Under aerobic conditions, the activities of acid invertase and sucrose synthase (cleavage) significantly decreased in conjunction with the decrease in non-reducing sugars and starch content in all the varieties. Disruption of starch biosynthesis under the influence of aerobic conditions in both leaves and grains and the higher build up of sugars possibly resulted in their favoured utilization in nitrogen metabolism. FengAiZan, PR115 and PR120 maintained higher levels of sucrose synthase enzymes in grains and leaves and contents of metabolites (amino acid, protein and non-reducing sugar) under aerobic conditions, while PR116, Punjab Mehak 1 and PAU201 performed better under transplanting conditions, thus showing their adaptation to environmental stress. Yield gap between aerobic and transplanting rice is attributed primarily to the difference in sink activity and strength. Overall, it appear that up-regulation of sucrose synthase (synthesis) and sucrose phosphate synthase under aerobic conditions might be responsible in enhancing growth and productivity of rice varieties.